Modeling and optimization of slag for copper capturing of Platinum group metals from Al2O3-based concentrate - Urtnasan, Erdenebold; Wang, Jei-Pil (International Journal of Innovative Research and Scientific Studies, 2025)
The mining of base metals, such as copper and nickel, frequently yields platinum group metals (PGMs) as byproducts, requiring specialized techniques for their extraction and purification. Platinum group metals (PGMs), found in concentrates with high aluminum oxide content, are associated within an aluminum oxide (Al₂O₃) matrix. The feasibility of dissolving platinum group metals (PGMs) in a metallic copper substrate was assessed through an investigation into the conversion of a platinum-bearing concentrate (72% aluminum oxide) to metallurgical slag. Within the CaO–SiO₂–Al₂O₃ partial equilibrium system, a thorough analysis was conducted to determine both the chemical composition and melting characteristics of the slag. Utilizing the Phase Diagram mode of Factsage software, a modeling of the slag structure at elevated temperatures was conducted, leading to the identification of an optimal slag composition exhibiting a reduced melting point. Based on the modeling conducted within the CaO–SiO₂–Al₂O₃ system, the optimal melting state of the slag was achieved at 1550 °C by fluxing with CaO and SiO₂ additions to reach a CaO/SiO₂ ratio of 0.7. The optimally melted slag, which was characterized by a CaO/SiO₂ ratio of 0.7, exhibited a morphology clearly indicative of the formation of an easily molten eutectic. A smelting experiment was conducted using 300 grams of concentrate, with the fluxing adjusted to a CaO/SiO₂ ratio of 0.7, successfully generating and maintaining a slag at a temperature of 1550 °C on a substrate of metallic copper. As a result, the copper matrix contained 111 mg/kg of Ag, 147 mg/kg of Pt, 213 mg/kg of Pd, and 204 mg/kg of Ir, a mix of PGMs.